Characteristics of neurogenic lower urinary tract dysfunction patients at Cipto Mangunkusumo Hospital (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Neurogenic lower urinary tract dysfunction (NLUTD) is an abnormal function of the bladder, urethra (and/or prostate in males) in patients with a clinically confirmed relevant neurologic disorder. Hence, accurate diagnosis and management of NLUTD is crucial. This study aimed to recognize the characteristics of NLUTD to identify, manage, and prevent the associated complications. METHODS This retrospective study was conducted at the Outpatient Clinic of the Department of Urology, Cipto Mangunkusumo Hospital, Jakarta, Indonesia, from January 2011 to December 2021. The study analyzed data collected from voiding dysfunction patients with upper motor neurological disorders who underwent urodynamic studies during the study period. Incomplete data in the medical records were excluded. RESULTS Mean age of the participants was 50.7 (18–95) years old. The most common cause of NLUTD was stroke (26.6%), followed by unspecified groups and spinal cord injury. Patients under 20 years old were affected by trauma and congenital defects. Of the patients, 34.0% had urinary retention, and 18.1% had incontinence. Small bladder capacity occurred in patients with stroke, Parkinson’s disease, and spinal/cerebral tumors, leading to decreased bladder compliance. CONCLUSIONS NLUTD was associated with aging, with upper motor neurological lesions such as trauma, stroke, and spinal/cerebral injury being the most common etiologies. Most patients with NLUTD had small bladder capacity and decreased compliance based on urodynamic result.